Gamification in e-learning: The mitigation role in technostress - Faridiah Aghadiati Fajri; RY. Kun Haribowo P.; Nurisqi Amalia; Dina Natasari (Institute of Advanced Engineering and Science, 2021)
The digital world demands graduates who are accustomed to deal with technology. Blended learning is one of the strategies by combining online media with face-to-face classes. It cannot be denied that students who interact with technology experience stress and tension. This condition have an impact on the learning process so that a way out is needed to bring it down. Gamification is a gaming technique that is applied to non-game applications to increase pleasure when interacting with these applications. This feature has been implemented in business applications, social media, e-commerce, and e-learning. However, the impact of playfulness in mitigating technostress has not been studied. This research examined the role of feedback mechanism and presentation mechanism in giving pleasure in LMS. Furthermore, this playfulness is expected to reduce the stress experienced by users. The research was conducted using a quasi-experimental method by giving participants time to follow the course with the gamification feature. The results showed that the gamification mechanism is able to provide pleasure which in turn will reduce the user's stress level. Based on the user-perceived of playfulness, gamification can reduce stress levels so it will reduce user resistance and increase the effectiveness of technology implementation.